On identifying the deceased in two-figured and multi-figured scenes of classical Attic funerary reliefs - Margariti, Katia (Journal of Greek Archaeology, 2016)
The major problem one faces when studying the iconography of classical Attic funerary reliefs is the identification of the deceased in scenes depicting more than one figure. Indeed, with the exception of two-figured scenes showing the deceased accompanied by a servant, it is often difficult (and at times even impossible) to identify the dead person with absolute certainty among the various figures depicted. The Athenian sculptors worked with a standard repertoire of themes that were considered suitable for grave reliefs, and these reliefs were usually bought ready-made by the family of the deceased upon visiting the sculptor’s workshop. Thus, the ambiguity of funerary relief scenes served the purpose of making the reliefs suitable for a wide range of customers. When there are no epigraphical clues as to the identity of the dead person, certain aspects of the iconography can be very helpful in identifying the deceased. The purpose of the present paper is to suggest and discuss such iconographical clues that may assist one in the arduous task of identifying the dead persons honoured by the grave reliefs. It should however be noted that not all of these clues can be applied to every scene, and therefore caution is always required when trying to interpret the iconography of funerary reliefs.